Accurate solid solution range of BiMnxFe3-xO6 and low temperature magnetism. (November 2017) - Jiang, Pengfei; Yue, Mufei; Cong, Rihong; Gao, Wenliang; Yang, Tao
Abstract: BiMn x Fe3- x O6 ( x = 1) represents a new type of oxide structure containing Bi 3+ and competing magnetic super-exchanges. In literature, multiple magnetic states were realized at low temperatures in BiMnFe2 O6, and the hypothetical parent compounds (BiMn3 O6, BiFe3 O6 ) were predicted to be different in magnetism. Herein, we performed a careful study on the syntheses of BiMn x Fe3- x O6 at ambient pressure, and the solid solution range was determined to be 0.9 ≤ x ≤ 1.3 by Rietveld refinements on high-quality powder X-ray diffraction data. Due to the very similar cationic size of Mn 3+ and Fe 3+, and possibly the structural rigidity, there was no significant structure change in the whole range of solid solution. The magnetic behavior of BiMn x Fe3- x O6 ( x = 1.2, 1.22, 1.26, 1.28 and 1.3) was generally similar to BiMnFe2 O6, while the relative higher concentration of Mn 3+ led to the decreasing of the antiferromagnetic ordering temperature. Graphical abstract: Highlights: The accurate solid solution range of BiMn x Fe3- x O6 is determined to 0.9 ≤ x ≤ 1.3. High quality XRD data were collected to prove the phase purity of BiMn x Fe3- x O6 . Rietveld refinements suggest the cationic substitution do not change the structure. Similar low temperature magnetism was observed for this series of oxides. The AFM ordering temperature decreased with the increasing the Mn 3+ content.